Carbohydrate mouth rinse improves cycling performance carried out until the volitional exhaustion - Bavaresco Gambassi, B.; Gomes de Santana Barros Leal, Y.; Pinheiro Dos Anjos, E. R.; Antonelli, B. A.; Gomes Gonçalves, E.; Silva, D. C.; Hermes Pires de Mélo Montenegro, I.; Di Cássia de Oliveira Angelo, R.; Suruagy Correia Moura, I.; Schwingel, P. A. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Carbohydrates (CHO) are among the most investigated nutritional ergogenic aids, and may be consumed in different forms, e.g., mouth rinse with carbohydrate solution (MRCS). In this sense, the aim of this study was to evaluate the impact of MRCS on the performance of physically active individuals undergoing a physical exercise session carried out until the volitional exhaustion. METHODS: This is a counter-balanced randomized study, with a double-blind design. The sample consisted of twenty-one physically active healthy men with a mean (±SD) of age of 22.4 (±2.7) years old, 76.7 (±6.0) cm of height,12.1% (±3.7) of body fat mass, and 23.9 (±2.4) kg/m2 of body mass index. After familiarizing the participants with the protocol (cycle ergometer, with oral mouth rinse procedure) and assessing the maximal lactate steady state the cycling exercise was performed until the volitional exhaustion in the following conditions: without mouth rinse (CONTROL), PLACEBO and MRCS. RESULTS: Time to reach exhaustion was statistically different (P<0.0001) between conditions (control: 43.0±27.5 minutes; placebo: 57.4±30.6 minutes; MRCS: 70.9±30.3 minutes). CONCLUSIONS: The administration of MRCS was shown to be effective in improving cycling performance, increasing the time to exhaustion until the volitional exhaustion. Thus, the use of methodology proposed by the present study may help coaches and practitioners improve the performance of physically active young adults.